2019
DOI: 10.3390/molecules24040794
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Proteomics Profiles Are Useful for Detection of Cancer Biomarkers and Changes Induced by Therapeutic Procedures

Abstract: Boron neutron capture therapy (BNCT) is a binary cancer treatment modality where two different agents (10B and thermal neutrons) have to be present to produce an effect. A dedicated trial design is necessary for early clinical trials. The concentration of 10B in tissues is an accepted surrogate to predict BNCT effects on tissues. Tissue, blood, and urines were sampled after infusion of two different boron carriers, namely BSH and BPA in the frame of the European Organisation for Research and Treatment of Cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 60 publications
2
27
0
Order By: Relevance
“…It has been suggested to play a role in stabilization of extracellular matrix by binding to hyaluronic acid, may be involved in modulating inflammation and inhibit apoptosis. Previous studies have identified ITIH4 as a potential diagnostic and prognostic marker for a number of diseases that include acute ischemic stroke, ovarian cancer, interstitial cystitis, liver fibrosis [ 23 ] and its increased levels were seen in cases of thyroid cancer [ 24 ]. The decrease in the abundance of ITIH4 in our study was confirmed by immunoblotting.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested to play a role in stabilization of extracellular matrix by binding to hyaluronic acid, may be involved in modulating inflammation and inhibit apoptosis. Previous studies have identified ITIH4 as a potential diagnostic and prognostic marker for a number of diseases that include acute ischemic stroke, ovarian cancer, interstitial cystitis, liver fibrosis [ 23 ] and its increased levels were seen in cases of thyroid cancer [ 24 ]. The decrease in the abundance of ITIH4 in our study was confirmed by immunoblotting.…”
Section: Discussionmentioning
confidence: 99%
“…renal glomerular diseases, allograft rejection, acute kidney injury (AKI), lupus nephritis, Fanconi syndrome and diabetes [20,22,23,24]. Elevated levels of urinary RBP4 are also observed in tuberculosis, head and neck cancers and bladder cancer [25,26,27]. It has not been yet established, whether particular concentration ranges of urinary RBP4 allow identi cation of speci c renal disorders, or help discriminate individuals with a renal/non-renal pathologies among healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…renal glomerular diseases, allograft rejection, acute kidney injury (AKI), lupus nephritis, Fanconi syndrome and diabetes [16,18,19,20). Elevated levels of urinary RBP4 are also observed in tuberculosis, head and neck cancers and bladder cancer [21,22,23]. It has not been yet established, whether particular concentration ranges of urinary RBP4 allow identi cation of speci c renal disorders, or help discriminate individuals with a renal/non-renal pathologies among healthy subjects.…”
Section: Discussionmentioning
confidence: 99%